A mutation within the SH2 domain of slp‐76 regulates the tissue distribution and cytokine production of iNKT cells in mice. Issue 9 (29th July 2016) - Danzer, Claudia; Koller, Anna; Baier, Julia; Arnold, Harald; Giessler, Claudia; Opoka, Robert; Schmidt, Stephanie; Willers, Maike; Mihai, Sidonia; Parsch, Hans; Wirtz, Stefan; Daniel, Christoph; et al.
Abstract : The adaptor protein slp‐76 regulates the tissue distribution of iNKT cells via ADAP‐dependent and ‐independent mechanisms. The reduced ADAP signal in slp‐76 ace/ace iNKT cells triggers the enhanced expression of CD11b and blocks the accumulation of iNKT cells in the spleen and liver. The concomitant, ADAP‐independent upregulation of neuropilin‐1 promotes the redistribution of iNKT cells to the peripheral lymph nodes Abstract : TCR ligation is critical for the selection, activation, and integrin expression of T lymphocytes. Here, we explored the role of the TCR adaptor protein slp‐76 on iNKT‐cell biology. Compared to B6 controls, slp‐76 ace/ace mice carrying a missense mutation (Thr428Ile) within the SH2‐domain of slp‐76 showed an increase in iNKT cells in the thymus and lymph nodes, but a decrease in iNKT cells in spleens and livers, along with reduced ADAP expression and cytokine response. A comparable reduction in iNKT cells was observed in the livers and spleens of ADAP‐deficient mice. Like ADAP −/− iNKT cells, slp‐76 ace/ace iNKT cells were characterized by enhanced CD11b expression, correlating with an impaired induction of the TCR immediate‐early gene Nur77 and a decreased adhesion to ICAM‐1. Furthermore, CD11b‐intrinsic effects inhibited cytokine release, concanavalin A‐mediated inflammation, and iNKT‐cell accumulation in the liver. Unlike B6 and ADAP −/− mice, the expression of the transcription factors Id3 and PLZF was reduced, whereas NP‐1‐expression was enhanced in slp‐76 ace/ace mice. Blockade of NP‐1 decreased the recovery of iNKT cells from peripheral lymph nodes, identifying NP‐1 as an iNKT‐cell‐specific adhesion factor. Thus, slp‐76 contributes to the regulation of the tissue distribution, PLZF, and cytokine expression of iNKT cells via ADAP‐dependent and ‐independent mechanisms.